Steps for individual providers to decrease mental health stigma in the emergency department: A narrative review - Chan, Eric C.; Breton, Holly; Smith, Jacqueline M; Grimminck, Rachel; Fedwick, Jason; Hilton, Emily (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2026)
Introduction: Stigmatization in mental illness can lead to negative consequences including reduced access to care, poorer physical outcomes and reduced willingness to seek help due to fear of judgment. Participants in previous studies have reported experiencing stigma following presentations to the emergency department (ED) for mental health-related reasons.Methods: This article aims to provide a brief, practical overview of data on stigma with a focus on results that can directly inform clinical practice. We searched PubMed to identify recurring topics in the literature on mental health stigma. Using search terms related to stigma and mental health, we screened 600 results to identify commonly discussed themes across the literature. Language and communication, stigmatizing beliefs around mental disorders, engagement with individuals with lived experience, and systemic factors contributing to interpersonal stigma were identified as frequently recurring themes. All papers were screened and those addressing at least one of the identified themes were read, with findings compiled to inform this review.Findings: We provide recommendations on language around mental health, including alternate ways of communicating to avoid labelling and foster a more collaborative approach to care. We also describe evidence that may address certain stigmatizing beliefs around mental disorders, including data to decrease pessimistic outlooks on disease prognosis. We also describe some principles around verbal de-escalation and trauma-informed care that can be incorporated into clinical practice. Given the importance of systemic issues in driving stigma, we also discuss some systemic factors contributing to the occurrence of interpersonal stigma in the ED.Conclusions: Providers should be encouraged to examine their language, beliefs and skillsets in relation to mental illness to improve their abilities to provide quality care for patients. Advocacy aimed at stimulating systematic change is also necessary to improve the healthcare system.